2014
DOI: 10.1098/rspb.2014.1776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ploidy and sex-locus genotype on gene expression patterns in the fire antSolenopsis invicta

Abstract: Males in many animal species differ greatly from females in morphology, physiology and behaviour. Ants, bees and wasps have a haplodiploid mechanism of sex determination whereby unfertilized eggs become males while fertilized eggs become females. However, many species also have a low frequency of diploid males, which are thought to develop from diploid eggs when individuals are homozygous at one or more sex determination loci. Diploid males are morphologically similar to haploids, though often larger and typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…By targeting the most relevant sensory organ associated with this behavior, our study provided better sensitivity to detect tissue-specific differences compared to similar studies which used the whole bodies of workers (Wang et al, 2008) and queens (Nipitwattanaphon, Wang, Dijkstra, & Keller, 2013). Other transcriptomics experiments have been conducted in fire ants in other contexts (Calkins et al, 2018;Chen, Shen, & Lee, 2006;Morandin et al, 2016;Nipitwattanaphon et al, 2014;Qiu et al, 2018). Our results and follow-up experiments uncovered an interesting, differentially expressed OBP, SiOB12b′, whose expression patterns suggest that it may play a role in the differences between monogyne and polygyne colony forms in fire ants.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting the most relevant sensory organ associated with this behavior, our study provided better sensitivity to detect tissue-specific differences compared to similar studies which used the whole bodies of workers (Wang et al, 2008) and queens (Nipitwattanaphon, Wang, Dijkstra, & Keller, 2013). Other transcriptomics experiments have been conducted in fire ants in other contexts (Calkins et al, 2018;Chen, Shen, & Lee, 2006;Morandin et al, 2016;Nipitwattanaphon et al, 2014;Qiu et al, 2018). Our results and follow-up experiments uncovered an interesting, differentially expressed OBP, SiOB12b′, whose expression patterns suggest that it may play a role in the differences between monogyne and polygyne colony forms in fire ants.…”
Section: Discussionmentioning
confidence: 99%
“…() compared gene expression in brains of honeybee males and females and reported that both sex and caste signals are involved in the gene regulation in male and female brains. Similar results have been demonstrated in the fire ant ( Solenopsis invicta ): the gene expression profiles in haploid males are very different from those of diploid females and even diploid males at three developmental time points (Nipitwattanaphon et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, little work has been done to characterize the genes present in the supergene region and to identify the mechanisms by which SB and Sb control the phenotypic differences between single‐ and multiple‐queen colonies. Studies using cDNA microarrays representing 3673 genes demonstrated that the supergene region is enriched for genes that are differentially expressed between queens (Nipitwattanaphon et al ) and workers (Wang et al , ) of the two colony types. This suggests that genes other than Gp‐9 could be responsible for the social dimorphism.…”
Section: Introductionmentioning
confidence: 99%